Making student voice heard in dialogic feedback: feedback design matters - To, Jessica; Aluquin, Dominique; Tan, Kelvin Heng Kiat (Frontiers in Education, 2025)
IntroductionMaking student voice heard is crucial for productive feedback. However, this is seldom in practice in the exam-oriented context because students lack opportunities and support to give voice in feedback processes. To bridge the gap, this collaborative action research explored how feedback could be redesigned to invite student voice in a Singapore secondary school.MethodologyWe collaborated with three Social Studies teachers to transform their error-focused practice into dialogic feedback accentuating student voice. Drawing on the Lundy model of participation and self-determination theory, the teachers designed a feedback log to let 48 secondary four (equivalent to Grade 10) learners articulate their voice and psychological needs for competence and relatedness.ResultsAnalysis of feedback logs, student focus groups and teacher interviews indicated three main aspects of student voice: (i) grades (numeric feedback) as an indicator to monitor one's goal achievement and exam preparation efforts; (ii) challenges in making feedforward; and (iii) learners' feedback engagement and motivation largely shaped by teacher response.DiscussionGiven the context-dependent nature of tasks in Social Studies, verbal reciprocal exchange would be useful in developing students' higher-order thinking skills for feedforward. Implications for productive feedback designs are discussed, and avenues for future research outlined.